Simulation of sea surface temperature (SST) and sea surface salinity (SSS) in the Bay of Bengal - Syamsul Rizal; . Muhammad; Taufiq Iskandar; Ichsan Setiawan; Agus Satriadi,; . Radinal (Syiah Kuala University, 2011)
The simulation of Bay of Bengal (included Andaman Sea) has been done. This investigation used equation of motion (Navier-Stokes equation). The equation of motion was solved by means of Hamburg Shelf Ocean Model (HAMSOM). The analysis is done for the year of 2007. The National Centers for Environmental Prediction (NCEP) data for year of 2007 is used to force the Bay of Bengal. The sea surface temperature (SST) and sea surface salinity (SSS) have been obtained and analyzed. The highest SST occurs in April 2007, while the lowest SST occurs in October 2007. The pattern of SST depends on the wind vector. From January untill June 2007, the SSS pattern is a west-east pattern. The SSS value is lower in the east and higher in the west. From July untill December, the higher value of SSS is generally in the middle of the Bay of Bengal. Generally, the value of SSS is higher in July and August, while in December and January the value of SSS is lower. Some results have been compared and consistent with the study of Vinayachandran dan Kurian (2008) and Vinayachandran and Yamagata (1998).